Developing online training in using music for carers of people with dementia: A focus group study. (23rd December 2021) - Garrido, Sandra; Markwell, Holly; Andreallo, Fiona; Hatcher, Deborah
Abstract: Objective: This study aimed to identify the core content and design issues in developing an online training course in the effective use of music for people with dementia. Methods: A co‐design approach was taken in which focus groups were conducted with aged care staff and family caregivers (n = 17; 76.5% female). A general inductive approach was taken to data analysis. The consolidated criteria for reporting qualitative research (COREQ) guidelines were followed to ensure rigour in this study. Results: Participants identified five core concepts for inclusion in the training program including the benefits of music, the need to assess for vulnerability to negative responses, music selection strategies, timing of use and equipment selection. Themes on design and implementation such as the need for role‐specific content for care staff at all levels and scenario‐based learning were identified. Conclusions: The development of online training in music use for carers of people with dementia needs to consider the demands on carers and develop training that is informative and engaging without placing large time demands on the user. Support at a management and executive level will be important to the implementation of such training in residential aged care contexts.